Alternative sources of biologically active substances - Bĕhal, V (Folia microbiologica, 2003)
The majority of antibiotics and substances with diverse biological activity used in medicine are produced by actinomycetes, nonfilamentous bacteria and fungi. Other microorganisms, such as myxobacteria, pseudomonads, nocardias, basidiomycetes, marine microorganisms, enterobacteria, halobacteria, hyperthermophiles etc. are investigated for new biologically active metabolites.
Keywords: houby; biologické přípravky; Bacteria; Anti-Bacterial Agents; Fungi; antibakteriální látky; Biological Products